Drivers of individual niche variation in coexisting species. (18th July 2018) - Costa‐Pereira, Raul; Rudolf, Volker H. W.; Souza, Franco L.; Araújo, Márcio S.
Abstract: Although neglected by classic niche theory, individual variation is now recognized as a prevalent phenomenon in nature with evolutionary and ecological relevance. Recent theory suggests that differences in individual variation across competitors can affect species coexistence and community patterns. However, the degree of individual variation is flexible across wild populations and we still know little about the ecological drivers of this variation across populations of single species and, especially, across coexisting species. Here, we aimed to (a) elucidate the major drivers of individual niche variation in natural communities and (b) to determine how consistent this variation is across coexisting species and communities. We analysed natural patterns of individual‐level niche variation in four species of coexisting generalist frogs across a wide range of tropical communities. Specifically, we used gut contents and stable isotopes (δ 13 C and δ 15 N) from frog species and their prey to quantify individual niche specialization. Then, we combined data on local community structure, availability of prey, phylogenetic relationships and predator–prey size models to test how this variation is related to four ecological factors which are predicted to be key drivers of individual specialization: intraspecific competition, interspecific competition, ecological opportunity (i.e., diversity of resources) and predation. We found that the degree of individual trophic specialization varied by up to ninefold across populations within the same species. This sizable variation in trophic specialization across populations was at least partially explained by gradients of density of competitors (both conspecifics and heterospecifics) and intraguild predation. However, the specific relationships between individual specialization and these ecological gradients were strongly species‐specific. As consequences, the identity of the species with more individual variation changed among sites and there was typically no spatial correlation in the degree of individual specialization across coexisting species. Our results show that individual niche specialization within and across species can be strongly context‐dependent and that hierarchies of individual variation among coexisting species are not necessarily consistent across communities. Recent theory suggests that this pattern could lead to concurrent changes in competitive interactions across sites and thereby could play a key role in species coexistence at the landscape level. Our results suggest that individual variation across and within coexisting species has the potential to affect not only species coexistence at local communities, but also regional diversity patterns. Abstract : The authors found that individual niche specialization is strongly context‐dependent and there is no consistent hierarchy of individual variation across species. These findings suggest that individual variation across and within coexisting species has the potential to affect not only species coexistence at local communities but also regional diversity patterns.